2022
DOI: 10.1007/s11469-021-00731-8
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship Between Youth Bullying and Internet Addiction? An Integrative Review

Abstract: Youth bullying is a global public health problem; Internet addiction is on the rise globally among youths. Because the linkage between these behaviors has not been clearly explicated, this integrative review evaluated the relevant empirical evidence. A search of five electronic databases identified 2,761 original citations published between January 2000 and May 2019. After further abstract screening and detailed evaluation of 262 full-text articles, the final sample consisted of 14 prospective descriptive stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 80 publications
(100 reference statements)
1
12
0
1
Order By: Relevance
“…Positive interpersonal interactions and relationships, in particular, can promote developments and adaptations, while negative interpersonal interactions and relationships will lead to adverse consequences, such as anxiety, depression, and so on [ 74 ]. Firstly, the results found that relational victimization was significant and positively associated with video game addiction among female college students, which is consistent with previous studies conducted in the general population or in males [ 24 , 75 ]. Regarding Internet use, it has been well-established that negative life events are distal causes of pathological Internet use based on the Cognitive-Behavioral model [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…Positive interpersonal interactions and relationships, in particular, can promote developments and adaptations, while negative interpersonal interactions and relationships will lead to adverse consequences, such as anxiety, depression, and so on [ 74 ]. Firstly, the results found that relational victimization was significant and positively associated with video game addiction among female college students, which is consistent with previous studies conducted in the general population or in males [ 24 , 75 ]. Regarding Internet use, it has been well-established that negative life events are distal causes of pathological Internet use based on the Cognitive-Behavioral model [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, PUSN has been found to be linked with BV. While BV has been associated with several types of addiction such as nicotine and alcohol dependence, it has also been linked to PUSN as a coping mechanism for dealing with stress and seeking comfort and support in digital world [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…School bullying, as one of the serious public health problems in adolescents, effective anti-school bullying interventions are needed in this population through school and family. When we examined the relationship between school bullying and VVGE in Chinese adolescents, we also found that moderate Internet addiction was correlated with both school bullying and VVGE, which indicated that Internet addiction might be a potential mediator in the association between school bullying and VVGE among Chinese adolescents and that VVGE might lead to Internet addiction among the youth, while adolescents addicted to the Internet were most likely to experience school bullying behaviors ( 38 ). Therefore, adolescents with Internet addiction signs should not be overlooked in the early stage of school bullying prevention programs or in preventing excessive video gaming of adolescents.…”
Section: Discussionmentioning
confidence: 94%